Towards an Information System on Environment - Lahiri, Abhijit (Journal of Information and Knowledge, 1978)
In India, activities concerning environment are dispersed between various departments both at the Centre and at State levels. Efforts in information generation and especially collation and processing activities have received new impetus. The information system on environment has been conceived as a part of the National Information System on Science and Technology (NISSAT) and will be built up with sub-systems at state and different government departments and agencies, research and academic institutions for a targetted set of users. Location and specific nature of the problems demand that instead of centralization of all information resources, the sub-systems be strengthened to take care of at least immediate feed-in and feed-back needs. Keeping this broad perspective in view, the design of the system will be attempted in three phases viz., (1) understanding of information requirements and feed-back needs, revitalization of information generation activities and streamlining the reporting system, (2) creation of the data base, and (3) development of analytical tools, with necessary facilities for link-up with the international systems like the International Referral system (IRS) and Global Environmental Monitoring System (GEMS). The article outlines an approach to the design.